2018
DOI: 10.1007/978-3-319-99654-7_5
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to Assess Indirect Environmental Effects of Digitalization Based on a Time-Use Perspective

Abstract: The digital transformation has direct and indirect effects on the environment. Direct effects are caused by the production, use and disposal of information and communication technology (ICT) hardware. Indirect effects include the changes to patterns of production and consumption enabled by ICT in other domains. Studies of indirect environmental effects of ICT often focus on individual applications domains and their use cases, which implies that these studies cannot capture systemic effects of ICT adoption. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…In order to assess indirect environmental effects, a mixed-method approach (e.g. combining LCA with social science methods) is required (Bieser & Hilty, 2018a).…”
Section: Resource Use Of Digitalisationmentioning
confidence: 99%
“…In order to assess indirect environmental effects, a mixed-method approach (e.g. combining LCA with social science methods) is required (Bieser & Hilty, 2018a).…”
Section: Resource Use Of Digitalisationmentioning
confidence: 99%
“…Furthermore, the saved travel costs can be used for other purposes (income rebound effects) and thus contribute to an increased use of resources [15]. Finally, co-workers can spend saved commute time on other activities that are associated with environmental impacts (time rebound effects [14]).…”
Section: Application Layermentioning
confidence: 99%
“…In order to realize these benefits, the choice of location of the CW space is in particular critical [11], [12], [13] However, CW can also increase environmental burdens, for example through required infrastructure to set-up and operate the CW space. It can also lead to rebound effects, if employees spend time and money saved on commuting on other activities, goods and services that are associated with environmental impacts [14]. In order to draw more specific conclusions about whether CW can contribute to an overall reduction in resource consumption, and which factors are particularly relevant, a more precise analysis is necessary [11], [15], [16], [17] One approach that has gained momentum in sustainability research is to test potentially sustainable innovations in living labs [18].…”
Section: Introductionmentioning
confidence: 99%
“…Studies comparing the life-cycle impacts of ICT on greenhouse gas emissions to the greenhouse gas abatement potential (due to enabling impacts) of the most relevant use cases have shown that the life-cycle impacts are usually smaller (e.g., [53,54]).…”
Section: Life-cycle Impactsmentioning
confidence: 99%